Mast cell stabilizers: from pathogenic roles to targeting therapies - Cao, Mengda; Gao, Yao (Frontiers in Immunology, 2024)
Mast cells (MCs) are bone-marrow-derived haematopoietic cells that are widely distributed in human tissues. When activated, they will release tryptase, histamine and other mediators that play major roles in a diverse array of diseases/disorders, including allergies, inflammation, cardiovascular diseases, autoimmune diseases, cancers and even death. The multiple pathological effects of MCs have made their stabilizers a research hotspot for the treatment of related diseases. To date, the clinically available MC stabilizers are limited. Considering the rapidly increasing incidence rate and widespread prevalence of MC-related diseases, a comprehensive reference is needed for the clinicians or researchers to identify and choose efficacious MC stabilizers. This review analyzes the mechanism of MC activation, and summarizes the progress made so far in the development of MC stabilizers. MC stabilizers are classified by the action mechanism here, including acting on cell surface receptors, disturbing signal transduction pathways and interfering exocytosis systems. Particular emphasis is placed on the clinical applications and the future development direction of MC stabilizers.